(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
This paper focuses on analyzing the properties of equilibrium points and limit cycles in two types of planar piecewise smooth slow-fast systems. The right-half system is a classical van der Pol equation, while the left-half system is either linear or quadratic. Additionally, we provide a detailed description of the characteristics of limit cycles in these systems.